POEMS syndrome: a unique presentation and a diagnostic challenge. Issue 12 (3rd December 2019) - Farrugia, Daniel; Camilleri, David James; Azzopardi, Janice; Camilleri, Franco
Abstract : We present the case of a previously well, 70-year-old lady who presented with gait deterioration and a clinicoradiological picture of myositis with T2-enhancement on MRI of the distal lower limb muscles. A muscle biopsy pointed towards neurogenic amyotrophy and a mixed demyelinating and axonal sensorimotor polyneuropathy was confirmed on nerve conduction studies. This was initially thought to be secondary to a myeloproliferative disorder but a positron emission tomography scan showed uptake in the left hip which corresponded to what was previously reported as a subchondral cyst on CT. A biopsy showed this to be a plasmacytoma in the context of a normal serum protein electrophoresis and a polyclonal increase in light chains on serum-free light chain estimation. The patient was started on treatment 6 months after the presentation for a diagnosis of POEMS syndrome, by which time, the patient had become bed-bound and fully dependent.